2014
DOI: 10.1111/bjd.12671
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo fluorescence confocal microscopy for fast evaluation of tumour margins during Mohs surgery

Abstract: The results demonstrate the feasibility of confocal mosaicing microscopy in fresh tissue for rapid surgical pathology, potentially to expedite and guide Mohs surgery with high accuracy. This observation is an important step towards the goal of using real-time surgical pathology for skin tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
110
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(118 citation statements)
references
References 14 publications
4
110
1
1
Order By: Relevance
“…Their result 30 is on par with and validates the results of the initial studies. 34 Micronodular/infiltrating BCC was the main histological subtype in this study.…”
Section: Confocal Mosaicking Microscopy Imaging Fromsupporting
confidence: 83%
See 2 more Smart Citations
“…Their result 30 is on par with and validates the results of the initial studies. 34 Micronodular/infiltrating BCC was the main histological subtype in this study.…”
Section: Confocal Mosaicking Microscopy Imaging Fromsupporting
confidence: 83%
“…Recently, Bennàssar et al 30 conducted another study, in the Mohs surgical setting, where-for the first time-true surgically excised fresh tissue margins from 80 BCC lesions (with or without tumors) were prospectively imaged with FCM. The goals of this study were (a) to evaluate the sensitivity and specificity of ex vivo FCM imaging in detecting residual BCC in Mohs tissue excisions and (b) to calculate the time invested up to the diagnosis for both FCM and frozen sections.…”
Section: Confocal Mosaicking Microscopy Imaging Frommentioning
confidence: 99%
See 1 more Smart Citation
“…FCM images offer nuclear-level resolution-similar to histopathologyand FCM does so in just a few minutes. [1][2][3][4][5] The microscope is commonly used in fluorescent mode with acridine orange, a contrast agent that specifically stains DNA and RNA and increases the contrast between the nuclear morphology and the surrounding background.…”
Section: Ex Vivo Fluorescence Confocal Microscopy In Conjunction Withmentioning
confidence: 99%
“…14 During MMS, RCM has been used to evaluate resection margins. 15,16 Analysis takes only 3 min, but with a sensitivity of 88% and specificity 99% in detecting BCC, 16 Professor Harwood presented a trial proposal for the surgical management of high-risk SCCs. With little or predominantly poor-quality literature and few trials in progress, a clinician survey for the National Institute for Health Research programme grant 'setting priorities and decreasing uncertainties' identified SCC management as a research priority.…”
mentioning
confidence: 99%